Returning Every Good to the Lord: The Ascetic Exemplarity of Francis of Assisi - Pansters, Krijn (Jewish Thought, 2021)
According to hagiography, Francis of Assisi (†1226) was not only a charismatic follower of Christ, but also an exemplary ascetic with many followers who were also followers of Christ. In his transition from a worldly way of life to a “practice of strict self-denial as a measure of personal and especially spiritual discipline” and “austerity in appearance, manner, or attitude” (Merriam-Webster), we discern three basic elements of asceticism: order, openness, and struggle. Francis seeks some form of outer and inner order, without which his practice and his project will not succeed; he maintains an openness toward the Lord and his neighbors, without which his life would remain unordered and meaningless; and he is involved in a continuous and burdensome struggle, without which his goal cannot be fulfilled. Behind his practice of strict self-denial and austerity, as described by his hagiographers, we discern three of spirituality: giving back, goodness, and God. In all three elements of asceticism and in all three elements of spirituality, we see religious exemplarity at work: Francis becomes an exceptional example to the men and women around him.